Factors influencing therapy choice and clinical outcome in cerebral venous sinus thrombosis - Dagmar Krajíčková (Nature Portfolio, 2020)
Abstract We aimed was to assess the factors influencing therapy choice and clinical outcome after 3–4 months in patients with cerebral venous sinus thrombosis (CVST). In a retrospective, bi-centric study, the set consisted of 82 consecutive CVST patients (61 females; mean age 33.5 ± 15.7 years). Following data were collected: baseline characteristics, presence of gender-specific risk factors (GSRF), location and extent of venous sinus impairment, clinical presentation, type of treatment, recanalization, presence of parenchymal lesions, and clinical outcome after 3–4 months (assessed using the modified Rankin Scale [mRS], with excellent outcome defined as mRS 0–1). Multivariate logistic regression analysis was used for statistical evaluation. After 3–4 months, complete recovery was achieved in 41 (50%) and excellent clinical outcome in 67 (81.7%) patients. Female sex (OR 0.11; p = 0.0189) and presence of focal neurologic deficit (OR 0.16; p = 0.0165) were identified as significant independent negative predictors and, the presence of GSRF (OR 15.63; p = 0.0011) as significant independent positive predictor of excellent clinical outcome. In conclusion, in our CVST patients, the presence of GSRF was associated with excellent clinical outcome, while the female sex itself was associated with poorer clinical outcome.